Characterization of the affective relationship between teachers and students with diverse capacities in the Sagrado Corazón de Jesús Educational Institution the Bethlemitas Sisters of the municipality of Filandia, Quindío, during the year 2019 (2021)
This research article is the product of the analysis carried out to characterize the affectivity between teachers and students with diverse abilities of basic primary in the Sacred Heart of Jesus School, in Filandia, Quindío. With the above, to work investigative, a mixed methodology was applied where the instruments used were surveys, interviews, class observation for teachers and students of the school; of Similarly, the analysis of results were applied to statistical graphs to measure the responses of teachers and students in the institution about the level of affectivity.